USING ONLINE LEARNING METHODS IN A COVID19 PANDEMIC SITUATION IN CLASS III INDONESIAN SUBJECTS OF MI TARBIYATUT THOLIBIN - Badzlina Nabilah Dhewi Wardina; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The use of online learning methods is the basis for educational policies by learning from home using and utilizing the internet occurs simultaneously and suddenly, which makes educators, students and parents panic, and everyone at home. This research is a qualitative research with the type of case study research. The research was conducted at MI Tarbiyatut Tholibin. The data analysis technique uses pattern matching techniques and making explanations and triangulation. The results students' responses to online learning were less enjoyable because the material presented was unclear, limited quotas, poor networks, application errors and lack of guidance by teachers. The implementation using the WhatsApp group chat application in the learning process according to the interests of the students. The advantages students feel more relaxed and happy, students feel they have more time at home with their families, more time to rest and relax and students feel more relaxed and less tense. The disadvantage The quota runs out quickly. Students find it more difficult to understand the material presented by the teacher. Students feel sad because the pocket money get is reduced and students feel that social activities with their friends are hampered.Keywords: Online learning method, covid-19 pandemic and Indonesian language